Efektivitas Teknik Scaffolding untuk Mengembangkan Strategi Metakognisi dalam Meningkatkan Keterampilan Mengeja Saat Menulis pada Anak ADHD - Putri, Asri Mutiara; Udaranti, Widayatri Sekka; Yuanita, Stephanie (ANFUSINA: Journal of Psychology, 2018)
Children with ADHD do not perform planning, monitoring, and evaluating process during writing task, therefore their writing product usually has low spelling accuracy. In this study, intervention was designed to improve spelling skill of children with ADHD while doing writing task by developing metacognitive strategy through scaffolding technique. This study is a single subject research with qualitative analysis to compare subject’s performance before and after intervention. The result of this study shows that scaffolding technique is effective in developing metacognitive strategy and improving spelling skill in writing task.